Quantitative detection of pork in commercial meat products by TaqMan® real-time PCR assay targeting the mitochondrial D-loop region. (1st November 2016) - Kim, Miju; Yoo, Insuk; Lee, Shin-Young; Hong, Yeun; Kim, Hae-Yeong
Highlights: Pork-specific primers and probe were developed using the mitochondrial D-loop region. TaqMan® real-time PCR was established for quantitative PCR detection of pork meat. The detection limit of this assay was 0.1 pg of DNA from heat-treated pork meat. Commercial meat products were used to verify the applicability of this method. Abstract: The TaqMan® real-time PCR assay using the mitochondrial D-loop region was developed for the quantitative detection of pork in processed meat products. The newly designed primers and probe specifically amplified pork without any cross-reactivity with non-target animal species. The limit of detection of the real-time PCR assay was 0.1 pg of heat-treated pork meat and 0.1% (w/w) pork meat in beef and chicken meat mixtures. The quantitative real-time PCR assay was applied to analyze the pork meat content in 22 commercial processed meat products including jerkies, press hams, sausages, hamburger patties and steaks, grilled short rib patties, and nuggets. The developed real-time PCR method was able to detect pork meat in various types of processed meat products that declared the use of pork meat on their label. All processed meat products that declared no use of pork meat showed a negative result in the assay. The method developed in this study showed sensitivity and specificity in the quantification of pork meat in commercial processed meat products.